Pengaruh Pertumbuhan Ekonomi, Tingkat Kemiskinan dan Indeks Pembangunan Manusia terhadap Tingkat Pengangguran Terbuka di Kabupaten Sidoarjo - Qorina Yuniarti; Niniek Imaningsih (Universitas Batanghari Jambi, 2022)
The problem of unemployment which has increased drastically and was in the highest position in East Java is the main target for solving the Sidoarjo Regency Government. This problem can obstruct development in the area. There are several factors causing the increase of Open Unemployment Rate, including Economic Growth, Poverty Rates, and the Human Development Index. The study was conducted to determine the effect of Economic Growth, Poverty Rate, and Human Development Index on the Open Unemployment Rate in Sidoarjo Regency for the period from 2006-2020. The research was conducted using data obtained through BPS (Central Statistics Agency) of Sidoarjo Regency and East Java Province. The analysis applied for this study is multiple linear regression and testing with the BLUE assumption was carried out in the study to prove the results that this study passed the classical assumption test. After going through the testing stage, all of the independent variables together showed a significant impact on the dependent variable, then partially only economic growth and poverty levels had a significant negative and significant positive effect, while the Human Development Index variable had no effect on the Open Unemployment Rate in Sidoarjo Regency.